2008
DOI: 10.1128/aem.02879-07
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Assessment of the Effects of the Broad-Spectrum Antimicrobial Chlorhexidine on the Outcome of River Microbial Biofilm Development

Abstract: Chlorhexidine is a common-use antibacterial agent found in a range of personal-care products. We used rotating annular reactors to cultivate river biofilms under the influence of chlorhexidine or its molar equivalent in nutrients. Studies of the degradation of [ 14 C]chlorhexidine demonstrated that no mineralization of the compound occurred. During studies with 100 g liter ؊1 chlorhexidine, significant changes were observed in the protozoan and micrometazoan populations, the algal and cyanobacterial biomass, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 43 publications
2
18
0
4
Order By: Relevance
“…in Bacteroidetes (Knarreborg et al, 2002;Young and Schmidt, 2004;Jernberg et al, 2005 (Antonopoulos et al, 2009;Rea et al, 2011). Lawrence et al have observed a significant reduction in the abundance of Betaproteobacteria and Gammaproteobacteria in river biofilm communities exposed to a broadspectrum antimicrobial chlorhexidine using fluorescent in situ hybridization (Lawrence et al, 2008), whereas no more information has been provided about the other bacteria groups in their research. Then in the study of Có rdova- Kreylos and Scow (2007), sulfate-reducing bacteria belonged to Deltaproteobacteria including Desulfovibrio, Desulfobacter and Desulfobulbus were obviously favored by ciprofloxacin in the sedimental microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…in Bacteroidetes (Knarreborg et al, 2002;Young and Schmidt, 2004;Jernberg et al, 2005 (Antonopoulos et al, 2009;Rea et al, 2011). Lawrence et al have observed a significant reduction in the abundance of Betaproteobacteria and Gammaproteobacteria in river biofilm communities exposed to a broadspectrum antimicrobial chlorhexidine using fluorescent in situ hybridization (Lawrence et al, 2008), whereas no more information has been provided about the other bacteria groups in their research. Then in the study of Có rdova- Kreylos and Scow (2007), sulfate-reducing bacteria belonged to Deltaproteobacteria including Desulfovibrio, Desulfobacter and Desulfobulbus were obviously favored by ciprofloxacin in the sedimental microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the limitations of this agent, (such as staining of the tooth surface, taste changes, and micro-biotic imbalances), other, naturally occurring agents have been investigated (Lawrence et al, 2008;Khan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Dengan adanya substrat maka biofilm terbentuk oleh inisiasi sel-sel bakteria, substansi eksopolisakarida (glikokaliks) yang digunakan untuk melekat akan menjadi pelekat dan atraktan bagi mikroorganisme lain termasuk alga (Lawrence et al, 2008). Bakteri, alga dan protozoa dan sebagainya selanjutnya akan membentuk biomassa perifiton, dengan demikian produktivitas primer kolom air yang sedikit rendah disebabkan sebagian Gambar 2.…”
Section: Hasil Dan Bahasanunclassified